Peningkatan Kompetensi Presentasi Mahasiswa melalui Pelatihan Penggunaan Aplikasi Prezi dalam Pembuatan Salindia Interaktif - Syamsurijal, Syamsurijal (JPPSD: Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
Presentation skills are essential skills that students must master to support academic and professional success. This study aims to analyze the effectiveness of Prezi application training in improving students' presentation skills in creating interactive slides. The research method used a quantitative approach with a quasi-experimental design involving 35 students as respondents. The data collection instrument was a five-point Likert scale questionnaire that measured technical mastery of Prezi, creativity in slide design, and presentation confidence. Data analysis used descriptive statistics and a paired sample t-test. The results showed a significant increase in presentation competency from an average score of 56.23 (pre-test) to 81.97 (post-test) with a t-value of 18.647 (p < 0.001). The dimension of technical mastery experienced the highest increase of 52.3%. The research instrument was valid and reliable with a Cronbach Alpha of 0.891. Student responses were very positive, with 91.4% stating that they were helped and 85.7% committed to continuing to use Prezi. This study concluded that Prezi training was effective in significantly improving students' presentation competency.